Passive Control of a Beam Subject to Travelling Inertial Load - Bajer, Cz.; Bogacz, R.; Imiełowski, Sz. (Engineering Transactions, 2000)
The subject of the study is the minimization of transverse vibration of elastic guideway excited by high-speed travelling inertial load. Two types of systems of passive control are considered, the post truss system and the dynamic vibration absorbers. In the first one, the beam is supported by posts fixed to the beam span and prestressed by tendons connected to the ends of beam. The considered system corresponds to the experimental test stand. It is modelled by a simply supported Bernoulli-Euler beam, where the material passive damping is represented by means of the Voigt model. In the system the control is performed by point transverse forces and bending moments applied to the beam span. The significant reduction of the amplitude of vibrations is achieved for a guideway supported by truss system consisting of two posts. The obtained results are compared with the data obtained for active control of the considered guideway.